2018
DOI: 10.1016/j.bjid.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of human T-lymphotropic viruses in West Africa

Abstract: Human T-lymphotropic viruses (HTLV) are Deltaretroviruses that infect millions of individuals worldwide via the same transmission routes as HIV. With the aim of exposing the possible re-emergence of HTLV in West Africa since discovery, a systematic review was carried out, focusing on the distribution of the virus types and significance of frequent indeterminate reports, while highlighting the need for mandatory routine blood screening. Capturing relevant data from discovery till date, sources searched were Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…8 HTLV-1 subtypes are associated with specific regions of the globe, while HTLV-2 subtypes are related to highly specific subpopulations and behaviour like injection drug use. 8 This study seems to be the first report of HTLV-1/2 prevalence in both healthy and diseased study groups in FCT, Nigeria. A previous study 7 was limited to HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 HTLV-1 subtypes are associated with specific regions of the globe, while HTLV-2 subtypes are related to highly specific subpopulations and behaviour like injection drug use. 8 This study seems to be the first report of HTLV-1/2 prevalence in both healthy and diseased study groups in FCT, Nigeria. A previous study 7 was limited to HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Abuja is a cosmopolitan city and the capital of Nigeria, characterized by high level of ethno-cultural diversity; this could therefore be the reason for the zero prevalence obtained from the study as ethno-cultural diversity and environmental differences have been found to be linked to the geographical variation in HTLV prevalence. 2,8 The limited number of study participants analysed could be the cause of zero prevalence obtained. The study participants also may not have been exposed to the viruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations